Delayed Development of Feeding Skills in Children with Feeding Difficulties—Cross-sectional Study in a Brazilian Reference Center - Ramos, Cláudia C.; Maximino, Priscila; Machado, Rachel H. V.; Bozzini, Ana Beatriz; Ribeiro, Letícia W.; Fisberg, Mauro (Frontiers in Pediatrics, 2017)
Background: Delays in gross motor development, sensory processing issues, organic and behavioral problems are known to interfere in the development of feeding skills (FS); and – therefore - in the success of the process of feeding a child. Children with feeding difficulties (FD) commonly present inadequacy of FS. Objectives: Assessment of five FS in Brazilian children with FD, and search of associations with types of FD. Methods: Cross-sectional study with 70 children below 10 years old. Data was obtained from medical records: age, gender, age at texture transitions, feeding phase (breastfeeding, weaning to solids or full solids) at first complaint; characteristics of the meal (duration, environment and shared meals with adults), self-feeding practices, use of feeding equipment and bottle, mouthing, feeding position and FD diagnosis. Skills were categorized according to standards for age. Chi-Square, Anova Test (or non-parametric equivalent) and Multinomial logistic regression tests were used, with a significance level of 5%. Results: There was no difference in FS (p>0,05) or in the number of FS inadequateness (p=0,84) according to FD diagnosis. The majority (94%) of children presented at least one delayed development of FS; 1/3 presented delays in more than half of the FS. The most prevalent inadequacies in FS were inadequate feeding position (73,5%), prolonged bottle feeding (56,9%) and inadequate self-feeding practices (37,9%). Feeding complaints first appeared at 10,9m ± 11,4, and picky eating was the most prevalent type of FD (37,1%). Most children were fed in inadequate environments (55,2%), without the company of adults (78%). Transition to solid foods occurred at 16m ± 5,6. Multinomial logistic regression showed no difference in likelihood of presenting any type of FD compared to picky eating, according to FS. Age at texture transition both from breastfeeding to complementary feeding (p=0,95), and from complementary feeding to solid foods (p=0,43) did not vary according to FD diagnosis. Conclusions: FS development or number of FS inadequateness did not vary according to FD diagnosis. Identification of these inadequacies could help the discussion for multi-professional treatment of patients with FD.